TOKUSUKE’S TENDENCY OF MASOCHISM AS REFLECTED IN JUNICHIRO TANIZAKI’S DIARY OF A MAD OLD MAN - Achmad Fanani (Unipdu Jombang, 2010)
Achmad Fanani University of Pesantren Tinggi Darul’Ulum Jombangakufanani@gmail.com Abstract Seventy-seven-year-old Tokusuke, a retired businessman, is the protagonist and diarist of this book. Various aches and pains plague him, but his spirits are buoyed by a growing erotic obsession with his daughter-in-law, Satsuko, a former nightclub dancer married to his workaholic son. She carelessly flirts with Tokusuke off and on. This short novel alternates between descriptions of our hero's haggling with the medical establishment and various medicines, fights with his wife and family, and encounters with Satsu. Considering some facts of his sexual behaviors it can be said that Tokusuke has a tendency of masochism. He has high sexual urges that last at least about six months. He also finds pleasure from being humiliated either physically or psychologically by beautiful women (Satsuko) whose character is bad for the compensation of sexual excitement. All these characteristics relate to the signs of masochism. key words: Masochism, sexual excitement Abstrak Tokusuke, pria berusia tujuh puluh tujuh tahun merupakan seorang pengusaha yang sudah pensiun. Dia adalah protagonis dan penulis buku Diary of A Mad Old Man. Meskipun berbagai penderitaan kerap menghampiri, akan tetapi semangatnya tetap berkobar oleh obsesi erotis terhadap menantunya, Satsuko, mantan penari hiburan malam, yang menikah dengan anaknya. Dia sering menggoda Tokusuke. Novel pendek ini bergantian menceritakan tentang petarungan Tokusuke dengan penyakitnya, pertengkaran dengan istri dan keluarganya, dan pertemuannya dengan Satsu. Melihat beberapa kenyataan tentang perilaku seksualnya, bisa dikatakan bahwa Tokusuke memiliki kecenderungan sebagai seorang masokis. Dia memiliki dorongan seksual yang kuat yang berlangsung selama 6 bulan berturut-turut. Dia juga senang disakiti baik secara fisik maupun mental oleh wanita cantik (Satsuko) yang memiliki karakter jelek dengan kompensasi kesenangan seksual. Semua karakter ini berkaitan dengan karakteristik seorang masokis. kata kunci: Masosisme, kesenangan seksual